Practice of Ethno medicine among the Chothe Tribe of Manipur North-East India - Cheithou Charles Yuhlung, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Practice of Ethno medicine among the Chothe Tribe of Manipur North-East India